Socially responsible landscape parks: A case study of landscape parks of Wielkopolskie voivodship - Magdalena Maćkowiak; Aleksandra Spychała; Sylwia Graja-Zwolińska (Studia Ecologiae et Bioethicae)
Initially, research on ‘social responsibility’ focused on the sphere of business (corporate social responsibility, CSR). However, taking into account the fact that social responsibility is connected with understanding society’s expectations in a broader perspective, the concept is now considered applicable to all organisations, not only business ones. The aim of this article is to draw attention to the problems in the socially responsible  functioning of landscape parks. The areas of activity of parks, for which specific legal, ethical or economic expectations may be formulated by various groups of stakeholders, are characterised. The results of pilot surveys carried out among employees of landscape parks in the Wielkopolskie voivodship are also presented.